Potensi Industri Bregasmalang – Petanglong dalam Mendukung Terciptanya Klaster Pendukung dan Bahan Baku Industri Pertahanan Indonesia - Endro Tri Susdarwono; Aswhar Anis (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2020)
The purpose of this study discusses the potential of the Bregasmalang - Petanglong industry in supporting the creation of supporting industry clusters and raw materials for the Indonesian Defense Industry. This research is a qualitative research, the type of research uses a comprehensive analytical study and analytical normative approach. The existing defense industryis expected to form defense industry clusters that drive the country's economic growth. The emergence of defense industry clusters in Indonesia will accommodate the workforce, so the defense industry is expected to contribute to reducing the unemployment rate in Indonesia. In the context of increasing investment and economic growth in the region which has an impact on regional and national economies, accelerated development includes the Brebes -Tegal-Pemalang Regions. To support and provide added value to the development of the area as intended, one of them is the Pekalongan - Batang area, hereinafter referred to as the Petanglong Area. The Defense Industri Law mixes that the defense industry consists of the main equipment industry, the main and supporting component industries, the component and support industries (supplies), and the raw materials industry. Keywords: Bregasmalang-Petanglong, Defense industry, Industrial potential, Raw material industry, Supporting industry